A New Hybrid Algorithm for Solving a System of Generalized Mixed Equilibrium Problems, Solving a Family of Quasi-𝜙-Asymptotically Nonexpansive Mappings, and Obtaining Common Fixed Points in Banach Space - J. F. Tan; S. S. Chang (International Journal of Mathematics and Mathematical Sciences)
The main purpose of this paper is to introduce a new hybrid iterative scheme for finding a common element of set of solutions for a system of generalized mixed equilibrium problems, set of common fixed points of a family of quasi-𝜙-asymptotically nonexpansive mappings, and null spaces of finite family of 𝛾-inverse strongly monotone mappings in a 2-uniformly convex and uniformly smooth real Banach space. The results presented in the paper improve and extend the corresponding results announced by some authors.